1978
DOI: 10.1002/bit.260200202
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the unit operations involved in the continuous flow isolation of β‐galactosidase from Escherichia coli

Abstract: SummaryA lo00 liter fermentor has been used to produce a continuous feed of Escherichia coli containing a high level of p-galactosidase. We have investigated the individual unit operations for the isolation of the enzyme :cell disruption, nucleic acid removal, protein precipitation, and solid-liquid separation after each stage. Using the information obtained we have been able to operate a semicontinuous process which when fully continuous would yield 100 g proteidhr, comprising 23% p-galactosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 18 publications
1
14
1
1
Order By: Relevance
“…The protein and DNA release analysis confirmed increased cell lysis in samples processed with the disc‐stack centrifuge as observed by other researchers [11]. In addition, agarose‐gel analysis indicated that released DNA was subjected to degradation.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The protein and DNA release analysis confirmed increased cell lysis in samples processed with the disc‐stack centrifuge as observed by other researchers [11]. In addition, agarose‐gel analysis indicated that released DNA was subjected to degradation.…”
Section: Resultssupporting
confidence: 81%
“…Results shown above indicated that the methods used at the cell harvest stage can have a substantial impact on SC plasmid yield and the level of contaminant DNA (chromosomal and degraded plasmid isoforms) entering the product stream. Previous studies with a disc‐stack centrifuge in the context of enzyme recovery have shown that decreases in product yield could be associated with premature cell lysis [10,11]. A series of experiments were performed with the dual objective of confirming that the decreased yield and increased contamination of disc‐stack‐centrifuge‐derived samples could be attributed to cell lysis and to establish a technique to characterize cells before proceeding to the lysis stage (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA concentrations in all of the process streams were predicted using a mass balance approach. Using data from a previous study (Higgins et al;[15]) it was assumed that the DNA remained soluble under the conditions used in the study. Figure 6 shows the average experimental and simulated DNA results for a number of small scale trials.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PEI has been used for the selective separation of nucleic acids from microbial cell extracts by precipitation [12][13][14]. Various other cationic agents had been used for the precipitation of nucleic acids: spermine, spermidine, cobalthexamine [15][16][17], divalent metal ions [18], and protamine sulfate (PS) [19,20].…”
Section: Introductionmentioning
confidence: 99%